2017
DOI: 10.18632/oncotarget.16797
|View full text |Cite
|
Sign up to set email alerts
|

Sequential evaluation of CALR mutant burden in patients with myeloproliferative neoplasms

Abstract: We investigated the variation of CALR-mutant burden during follow-up in 105 CALR-mutant MPN and compared it to the variation of JAK2-mutant burden in 226 JAK2-mutant MPN.The median allele burden at last evaluation was significantly higher than at first evaluation in essential thrombocythemia (ET) (49.5% vs 45%, P < .001) but not in primary myelofibrosis (PMF) (52% vs 51%, P 0.398). Median values of slope were positive both in ET (0.071) and in PMF (0.032). In CALR-mutant ET there was a difference between natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Anyway, 19pLOH appears to be a relatively uncommon event [ 37 ], in contrast with 9pLOH in JAK2 -mutant MPN and 1pLOH in MPL -mutant MPN [ 8 , 38 , 39 ]. It has been suggested that the clonal expansion in CALR -mutant MPN is faster than that observed in JAK2 -mutant MPN [ 40 ].…”
Section: Mutation and Clinical Phenotypementioning
confidence: 99%
“…Anyway, 19pLOH appears to be a relatively uncommon event [ 37 ], in contrast with 9pLOH in JAK2 -mutant MPN and 1pLOH in MPL -mutant MPN [ 8 , 38 , 39 ]. It has been suggested that the clonal expansion in CALR -mutant MPN is faster than that observed in JAK2 -mutant MPN [ 40 ].…”
Section: Mutation and Clinical Phenotypementioning
confidence: 99%
“…4750 CALR mutations appear to confer a greater proliferative advantage to the neoplastic clone compared with JAK2 mutations; clonal expansion is faster in CALR -mutated cases than in JAK2 -mutated cases, both in ET and in PMF. 51…”
Section: Essential Thrombocythemia: State Of the Art Updatementioning
confidence: 99%
“…The mutations all share the characteristic of affecting the JAK‐STAT signal transduction pathway generating the classic MPN phenotype, with activation and proliferation of the haematopoietic progenitor cell, and uncontrolled production of different terminal blood cell quantities, depending on MPN subtype and mutation type (Shallis et al, 2020 ). In the JAK2 and CALR positive, a steady increase in the mutational allele burden (“tumour” burden) is seen over the biological continuum for MPNs from the early‐stage disease to the advanced burned out PMF stage (Cavalloni et al, 2017 ; Hasselbalch, 2013 ).…”
Section: Introductionmentioning
confidence: 99%